Odpowiedzi

2010-02-08T17:23:37+01:00
(-p2-q2+1)+(-9+p2+q2)=
-p²-q²+1-9+p²+q² =
= -8

(2k2-k)-(11-9k-3k2)=
2k²-k-11+9k+3k² =
= 5k²+8k-11

(7mk+3m+4k)-(-5k+4m-mk)=
7mk+3m+4k+5k-4m+mk=
8mk-m+9k
2010-02-08T17:27:41+01:00
(-p2-q2+1)+(-9+p2+q2)=
-p2-q2+1-9+p2+q2=-8


(7mk+3m+4k)-(-5k+4m-mk)= 7mk+3m+4k+5k-4m+mk= 8mk-1m+9k


2010-02-08T17:29:51+01:00
1.(-p2-q2+1)+(-9+p2+q2)=-p2 - q2 +1-9+p2+q2= -8
2.(2k2-k)-(11-9k-3k2)= 2k2 - k-11+9k+3k2=5k2-11+8k
3.(7mk+3m+4k)-(-5k+4m-mk)= 7mk+3m+4k+5k-4m+mk=8mk-4m+9k